Long-term immune deficiency after allogeneic stem cell transplantation: B-cell deficiency is associated with late infections - Corre, Elise (Ferrata Storti Foundation, 2010)
Immune reconstitution was analyzed in 140 consecutive patients who were 2-year disease-free and who underwent myeloablative allogeneic transplantation. A CD4 and CD8 defect was observed involving naive, terminally differentiated, memory and competent cells and above limits values for activated subsets. Natural killer cells normalize at six months while we observed expansion of CD19(+)/CD5(+) B cells after three months and a persisting defect of memory B cells. Chronic graft-versus-host disease did not influence significantly those parameters for CD8 subsets while the naïve and competent CD4 subsets were strongly affected. But the most profound impact of chronic graft-versus-host disease was on B-cell subsets, especially on the memory B population. The cumulative incidence of late severe infections was low (14% at four years). Using Cox’s models, only low B-cell counts at 12 (P=0.02) and 24 (P=0.001) months were associated with the hazard of developing late infection, in particular if patients did not develop chronic graft-versus-host disease.